The Burden of Ventricular Premature Complex Is Associated With Cardiovascular Mortality - Lee, Po-Tseng; Huang, Ting-Chun; Huang, Mu-Hsiang; Hsu, Ling-Wei; Su, Pei-Fang; Liu, Yen-Wen; Hung, Meng-Hsuan; Liu, Ping-Yen (Frontiers in Cardiovascular Medicine, 2022)
Background Ventricular premature complex (VPC) is one of the most common ventricular arrhythmias. The presence of VPC is associated with an increased risk of heart failure (HF). Method We designed a single-center, retrospective, and large population-based cohort to clarify the role of VPC burden in long-term prognosis in Taiwan. We analyzed the database from the National Cheng Kung University Hospital-Electronic Medical Record (NCKUH-EMR) and NCKUH-Holter (NCKUH-Holter). A total of 19,527 patients who underwent 24-h Holter ECG monitoring due to palpitation, syncope, and clinical suspicion of arrhythmias were enrolled in this study. Results The clinical outcome of interests involved 5.65% noncardiovascular death and 1.53% cardiovascular-specific deaths between 2011 and 2018. Multivariate Cox regression analysis, Fine and Gray's competing risk model, and propensity score matching demonstrated that both moderate (1,000–10,000/day) and high (>10,000/day) VPC burdens contributed to cardiovascular death in comparison with a low VPC burden (<1,000/day). Conclusion A higher VPC burden via Holter ECG is an independent risk factor of cardiovascular mortality.